A REVIEW ON EMERGENCE OF ANTIBIOTIC RESISTANT Staphylococcus aureus AND ROLE OF CHITOSAN NANOPARTICLE IN DRUG DELIVERY: Pharmaceutical Sciences-Novel drug delivery system - PRASAD CHAKRABORTY, SUBHANKARI; PRAMANIK, PANCHANAN; ROY, SOMENATH (International Journal of Life Science and Pharma Research, 2012)
Staphylococcus aureus is a most common pathogen in hospital and community acquired disease that causes a wide range of infection such as skin and soft tissue infection to life threatening disease like respiratory tract infection, musculoskeletal infection, endocarditis and urinary tract infection. More than 90% of Staphylococcus strains are resistant to penicillin. In 1961 S. aureus developed resistance to methicillin (MRSA), invalidating almost all antibiotics, including the most potent β-lactams. Vancomycin, a glycopeptide antibiotic, was used for the treatment of MRSA in 1980. Vancomycin inhibits the bio-synthesis of peptidoglycan and the assembly of NAM-NAG-polypeptide into the growing peptidoglycan chain. Vancomycin resistant S. aureus (VRSA) first appeared in the USA in 2002. Increasing resistance of S. aureus to last line of drug i.e., vancomycin highlights the need for either the development of new and novel antibiotics or the improvement of efficacy of established antibiotics by the development of new agents capable of enhancing antibiotic activity. A Chitosan nanoparticle delivers anti-infective drugs such as antibacterial, antiviral, antifungal and antiparasitic drugs. In the present review the antibiotic emergence of Staphylococcus aureus, formulation techniques of chitosan nanoparticles and different biological profits of chitosan nanoparticles are discussed.